NCEP FNL Operational Model Global Tropospheric Analyses, April 1997 through June 2007 - National Centers For Environmental Prediction/National Weather Service/NOAA/U.S. Department Of Commerce (UCAR/NCAR - Research Data Archive, 1997)
The Final (FNL) global tropospheric analyses archived here were produced by NCEP's Global Forecast System (GFS), which was run operationally at 12-hour intervals to make multiple-day weather forecasts, from April 1997 through June 2007. FNLs are analyses that are produced after the model has completed the forecast cycle, and they include the most complete set of observations available for a given cycle. The FNL from a given cycle, which is the best available analysis, is then used in the initialization of the next cycle. FNL Data are available on pairs of 2.5-degree hemispheric grids (North and South) at the Earth's surface, sixteen vertical levels from 1000 millibars up to 10 millibars, the tropopause, boundary layer, two subsurface levels, and a few others. Parameters include surface pressure, sea level pressure, geopotential height, temperature, sea surface temperature, potential temperature, relative humidity, snow depth (weekly, Northern Hemisphere only) precipitable water, u- and v- winds, and vertical motion.